2018
DOI: 10.1590/s1980-220x2017048703377
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with family risk of children with special health care needs

Abstract: Objective: To identify the factors associated with family risk of children with special health care needs. Methods: Bicentric study, with a cross-sectional design and a quantitative approach, with family caregivers of children with special health care needs. Instruments were applied to obtain a sociodemographic characterization, and identify and classify the family risk. For analysis between variables, Mann-Whitney and Fisher’s exact tests were used and the Spearman’s correlation coefficient was calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 15 publications
0
7
0
13
Order By: Relevance
“…In the same perspective, a study with a quantitative approach carried out with 100 caregiving mothers of CRIANES identified that, although most of them were married or in a stable relationship, this condition did not influence the reduction of their physical, emotional and social burden ( 6 ) . On the other hand, a statistically significant association was observed between marital status and family risk, that is, caregiving mothers who had the presence of a partner had a reduced family risk and less social vulnerability ( 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the same perspective, a study with a quantitative approach carried out with 100 caregiving mothers of CRIANES identified that, although most of them were married or in a stable relationship, this condition did not influence the reduction of their physical, emotional and social burden ( 6 ) . On the other hand, a statistically significant association was observed between marital status and family risk, that is, caregiving mothers who had the presence of a partner had a reduced family risk and less social vulnerability ( 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…National studies demonstrate that the daily life of CSHCN families is marked by efforts and difficulties that transcend the child's clinical fragility, such as social vulnerability, low income, and low level of education of caregivers (24)(25) . Socioeconomic factors have hindered the access of these patients and their families to health services, causing inequities in access (26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 For being children who require complex and continuous health care, the family needs to incorporate new knowledge and practices into everyday life. 23 The desire to breastfeed the child drives them to overcome the barriers. Being able to breastfeed and establish body-to-body contact maximized the bond and the exchange of affection between mother and child, giving rise to feelings that conferred pleasure, satisfaction, empowerment, joy, accomplishment, and self-confidence, among others.…”
Section: Discussionmentioning
confidence: 99%